Dynamics of roughness and surface reactions at solid electrodes - Arvia, Alejandro Jorge (1992)
Surface disorder and random roughness of electrode surfaces are discussed in terms of Euclidean and fractal models. Roughness development at different metals results from two contributions operating in opposite directions, namely shadowing between growing clusters which leads to rough surfaces, and surface diffusion phenomena which tend to smooth surface irregularities. The second contribution depends on the specific mobility of the deposited metal atoms, the temperature, and the electrolyte composition. Monte Carlo simulations based upon nucleation and growth models show that the growth processes controlled by either surface reactions or mass transport of reacting species, including surface diffusion, produce compact deposits with a weak surface disorder. Conversely, the growth process under mass transport control involving a negligible surface diffusion generates open structures with a strong surface disorder. Rough metal deposits exhibiting a fractal behaviour are considered. The fractal dimension provides a quantitative description of the degree of disorder, the growth mechanism and the reactivity of those surfaces in relation to electrocatalysis.